Detection of Neospora caninum IgG antibodies in goats in Elazig, Erzurum and Kırsehir provinces of Turkey - Utuk, A.E.; Simsek, S.; Piskin, F.C.; Balkaya, I. (My University, 2011)
The aim of this study was to detect Neospora caninum IgG antibodies in Saanen and Hair goats from Elazig, Erzurum and Ki{dotless}rsehir provinces of Turkey. For this, a total of 128 sera obtained from goats were tested using a commercially available competitive enzyme-linked immunosorbent assay (c-ELISA) kit. Overall prevalence of anti-N.caninum antibodies was 10.2% (13/128); and mean prevalence in Hair and Saanen goats were 13.8% (12/87) and 2.4% (1/41) respectively. Tis is the frst serological study on caprine neosporosis in the above mentioned provinces of Turkey.
Keywords: c-ELISA; Goat; Neospora Caninum; Turkey